Exploring the genetic makeup of Xanthomonas species causing bacterial spot in Taiwan: evidence of population shift and local adaptation - Chen, Jaw-Rong; Aguirre-Carvajal, Kevin; Xue, Dao-Yuan; Chang, Hung-Chia; Arone-Maxwell, Lourena; Lin, Ya-Ping; Armijos-Jaramillo, Vinicio; Oliva, Ricardo (Frontiers in Microbiology, 2024)
The introduction of plant pathogens can quickly reshape disease dynamics in island agro-ecologies, representing a continuous challenge for local crop management strategies. Xanthomonas pathogens causing tomato bacterial spot were probably introduced in Taiwan several decades ago, creating a unique opportunity to study the genetic makeup and adaptive response of this alien population. We examined the phenotypic and genotypic identity of 669 pathogen entries collected across different regions of Taiwan in the last three decades. The analysis detected a major population shift, where X. euvesicatoria and X. vesicatoria races T1 and T2 were replaced by new races of X. perforans. After its introduction, race T4 quickly became dominant in all tomato-growing areas of the island. The genomic analysis of 317 global genomes indicates that the Xanthomonas population in Taiwan has a narrow genetic background, most likely resulting from a small number of colonization events. However, despite the apparent genetic uniformity, X. perforans race T4 shows multiple phenotypic responses in tomato lines. Additionally, an indepth analysis of effector composition suggests diversification in response to local adaptation. These include unique mutations on avrXv3 which might allow the pathogen to overcome Xv3/Rx4 resistance gene. The findings underscore the dynamic evolution of a pathogen when introduced in a semi-isolated environment and provide insights into the potential management strategies for this important disease of tomato. Keywords Bacterial spot, local adaptation, diversification, pathogen introduction, effectors INTRODUCTION Tomato (Solanum lycopersicum L.) is one of the most important vegetable crops worldwide. Yet, most tomato-growing areas are challenged by bacterial spot caused by Xanthomonas species. This disease